MODELISATION DU PLAN D’URBANISME DE LA VILLE D’EL EULMA (ALGÉRIE). APPORT DE L’INTELLIGENCE TERRITORIALE DANS LA GOUVERNANCE URBAINE - AKAKBA AHMED; KALLA MAHDI; DRIDI HADDA; FILLALI ABDELWAHHAB (Revue Roumaine de Géographie)
Modelling the urbanism plan of El Eulma town (Algeria). The contribution of territorial knowhow to urban governance. All Algerian cities have great difficulties to implement coherent management plans. This difficulty is mainly stemming from the weakness of information control and the lack of coordination between the different actors. Here appears that the availability of abundant spatial structured manageable and standard information, allowed by geomatic techniques, is essential for mastering the space and improving performances in the territorial management. The advantage of this approach lies in the ability of exploiting geometric and attributes data, to perform a variety of analyses in terms of proximity, superposition and autocorrelation. In order to show the interest and the role of geomatics in planning and implementing management plans, this study illustrates three applications: determining the extension areas, assessing the distribution of public facilities, as well as industrial risk evaluation. Therefore, the numerical approach through these three examples, demonstrates the effectiveness of these spatialization tools in terms of planning.